Citizen engagement with information aggregation markets. (17th October 2012) - Bothos, Efthimios; Apostolou, Dimitris; Mentzas, Gregoris
Participatory governance entails converting citizens from passive users of administrative decisions into active participants in political procedures. Public institutions and organisations can benefit from methods and tools able to aggregate and interpret information dispersed among citizens. In this paper, we explore the use of Information Aggregation Markets (IAMs) for citizen engagement. We identify the benefits of IAMs and explain how markets can be used to aggregate citizens' opinions and views on policy issues. Furthermore, we report on two real life cases where we deployed IAMs to assist the decision–making processes of public organisations. The positive feedback from participants and decision–makers provides empirical evidence on the benefits of IAMs as a method for engaging citizens in public policy decision–making.